Location Specific Perceptions And Adoption Of The Health Management Information System (Hmis) Among Esic Patients In The Tirunelveli Sub-Region: A Quantitative Approach To Understand The Adoption Patterns - Dr. C.Sriram; Dr. C.Pichaandy (International Journal of Advanced Science and Technology, 2020)
India’s Health Management Information System (HMIS) is just as much an effort to employ technology to improve people’s health. Further, it is a mission to convince health workers that good data can pave the way to better health care. Home to a surging population of more than one billion people spread throughout megacities and 600,000 villages, India faces health care challenges of a scale and diversity unmatched in the developing world. The country’s economy has surged in recent years and technology based industries thrive in major Indian cities. In addition, the central government seeks to attract foreign investment in the healthcare sector. Health systems across the globe are struggling with growing costs and the ability to provide quality care for all their citizens. The problems that HMIS addresses are not country-specific, but universal concerns. As a result, unlike most other approaches that may not be as broadly applicable, HMIS has garnered enthusiasm as a universally accepted tool to improve health care delivery. As both the need for HMIS and the available types of technology grow, the question is no longer whether a country should adopt these new technologies, but when and how they can be harnessed to make significant improvements in health care. This study revealed that location of patients influenced health management information system adoption among Employees’ State Insurance Corporation (ESIC) patients in the Tirunelveli sub-region. Survey method was used in this quantitative study. The questionnaire was translated to the local language (Tamil) for easy understanding and personally distributed by the researcher to the ESIC patients in the Tirunelveli sub-region (Tirunelveli, Tuticorin and Kanyakumari districts). For statistical hypothesis testing, the available survey results were compared against the null hypotheses and the statistical tools involved in carrying out this study include the ‘t’ test and the chi-square test of association. The study results stated that location can also play a key role in helping ESIC patients learn how to best adopt the HMIS software quickly. Accordingly, replacing paper-based medical records with HMIS can facilitate timely access to, and better transmission of, patient medical information across the health care continuum. This is likely to directly raise the quality of care by improving clinical decisions and avoiding errors. Further, Health Management Information System (HMIS) interfaces technology with the existing combination of people and procedures that make